Faktor-Faktor Penyebab Putus Sekolah pada Jenjang SMP di Dusun Genurid Desa Kawengen Kecamatan Ungaran Timur - Louis Naernia; Yustinus Windrawanto (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the factors that influence the decision to drop out of school among students in Genurid Hamlet using Bernard Weiner (dalam Ardianita, 2024)'s Attribution Theory perspective. This study is a descriptive qualitative study of five participants who dropped out of junior high school (SMP). Data were collected through in-depth interviews and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that the decision to drop out of school is the result of an interaction between internal and external factors, including task difficulty, ability, effort, and luck (circumstances beyond an individual's control). Participants perceived mathematics as a difficult subject, attributed failure to their own limitations in ability, and showed low learning engagement. In addition, family conditions, low parental education levels, experiences of failing a grade, economic factors, and family mindsets toward education also influenced this decision. This study confirms that dropping out of school is not only influenced by structural factors, but also by cognitive processes and the family environment, which are interrelated.